FILSAFAT DIALOGIS MARTIN BUBER DALAM MERAWAT TANGGUNG JAWAB DI TENGAH PANDEMI COVID-19 - Patrisius Epin Du; Yakobus Syukur (Lumen Veritatis: Jurnal Filsafat dan Teologi, 2021)
The focus of this paper is to discuss Martin Buber's dialogical philosophy, namely the relation I and It, I andThou and its relevance to caring for the value of responsibility in the midst of the Covid-19 pandemic. For some people, the Covid-19 pandemic is an opportunity to profit at the expense of others. Some time ago the public was enlivened with news about corruption in social assistance funds and used antigen tests. This event shows a crisis of awareness of the meaning of one's existence to others around him. Other people are considered as objects for the sake of economic interest alone. Therefore, Martin Buber's idea seeks to reawaken awareness about the relationship between human beings. Through his dialogical philosophy he explains that the other is a part of me and I am responsible for it. The method used in this paper is a critical analysis of Martin Buber's philosophical thinking and its relevance in fostering a sense of responsibility in the midst of the Covid-19 pandemic. The finding in this article are that others are part of me and their presence is a blessing for me so that I must be responsible for others.